Pengaruh corporate governance dan issue characteristics terhadap yield obligasi - MARIA MARIA (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2016)
The purpose of this study was to obtain empirical evidence that the independent directors, audit committee, institutional ownership, managerial ownership, sinking fund and years to maturity effect on bond yields. Bond yields were used in this study is the yield to maturity. To conduct research on bond yields, the researchers also used 38 samples. The results showed that the independent directors, audit committee, sinking fund and years to maturity effect on bond yields. While managerial ownership and institutional ownership have no effect on bond yields.